The Contribution of Event-Related Potentials to the Understanding of Sign Language Processing and Production in the Brain: Experimental Evidence and Future Directions - Hernández, Doris; Puupponen, Anna; Jantunen, Tommi (Frontiers in Communication, 2022)
Functional neuroimaging allows investigation of the timing properties of the brain mechanisms underlying covert language processing. This paper presents a review of the use of the neuroimaging technique called Event-Related Potentials (ERPs) in sign language (SL) research. In the field of neurolinguistics, ERPs have been widely used in the study of spoken language, but their use in SL is still rare. Studying the neurocognitive aspects of SL could lead to a better understanding of the specific processing of SL in the brain. This review outlines the basic theoretical and methodological principles of ERPs. We focus on three groups of ERPs that are particularly relevant to SL processing and production: ERPs focusing on cognition, ERPs focusing on language, and ERPs focusing on movement aspects. We then summarize within each group some ERPs that we consider could be useful for studying the sequence of cognitive processes underlying SL processing and we discuss the current state of the use of ERPs within SL research. According to our analysis of the field, ERPs focusing on language aspects have been used more than ERPs focusing on cognitive and movement-related aspects to study SL. More variability in the type of SLs used is needed to expand the inferences made so far. For the development of the field, we recommend the more frequent use of videos and SL stimulation at a natural pace in order to understand how SL is processed in daily life. The use of a wider variety of ERPs in the study of SL is also recommended. We conclude that ERPs offer a useful tool to address unanswered questions in the field, especially those that call for measuring the building blocks of SL processing in real time. The study of SL cognitive processing in the brain is still in its infancy. One way of developing the field in the coming years would be the more frequent use of the ERP neuroimaging technique.